Career management strategies and decisions of female leaders - Jedlička, Natalie; Pauknerová, Daniela, 1970-; Jarošová, Eva, 1955-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This Master’s Thesis aims to explore various career management strategies of females in leadership or management positions. The methodology used to attain this goal has the form of in-depth interviews, which were conducted with 8 women in leadership positions from the Czech Republic. The results of the interviews were then analysed, and 7 themes were identified. The findings revealed similarities and differences in the female's approaches towards their career management. Such as that mentors played an important role in the career development of nearly all the females, however hardly any of them used their network to achieve the position they are in today. The interviewed women shared their career aspirations, career development tools, obstacles and challenges they experienced during their professional path, which enabled the formulation of recommendations for other women that consider a management position.
Vedoucí práce: Daniela Pauknerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses